Thomas Mann und der Protestantismus: 100 Jahre »Buddenbrooks« - Rohls, Jan (Zeitschrift für Theologie und Kirche, 2002)
Thomas Mann saw himself as a Protestant writer. In this article, the author attempts to show the kind of Protestantism he advocated and how his Protestantism was expressed in his different novels and other writings.